The SAVI programme in Nigeria: Towards politically smart, locally led devlopment - Booth, David; Chambers, Victoria (ODI, 2014)
? More examples are needed of aid programming that works by being resp onsive to country realities: politically smart, problem-driven and loc ally led ? DFID’s SAVI programme has revealed a hitherto untapped pote ntial for change leading to better development results at state level in Nigeria ? SAVI provides low-profile support to state-level organisa tions and partnerships, building their capacity to engage constructive ly with government ? It avoid the pitfalls of a donor-driven approach by ‘taking the money off the table’ ? This illustrates the power of fa cilitated multi-stakeholder engagement and the disadvantages of seeing this in terms of ‘supply side’ and ‘demand side’ governance ? The set -up of the DFID suite of state-level programmes, with separately manag ed sector support and ‘governance’ initiatives, has limited realisatio n of the potential ? Key enabling conditions were that DFID provided s pace for an experience-based design process and permitted tangible res ults to be judged retrospectively, not pre-programmed